2001
DOI: 10.1128/aem.67.9.3860-3865.2001
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Environmental Release of a Sinorhizobium meliloti Strain Genetically Modified To Be More Competitive for Alfalfa Nodulation

Abstract: ؊ mutant strain, that proline dehydrogenase activity is required for colonization and therefore for the nodulation efficiency and competitiveness of S. meliloti on alfalfa roots (J. I. Jiménez-Zurdo, P. van Dillewijn, M. J. Soto, M. R. de Felipe, J. Olivares, and N. Toro, Mol. Plant-Microbe Interact. 8:492-498, 1995). In this work, we investigated whether the putA gene could be used as a means of increasing the competitiveness of S. meliloti strains. We produced a construct in which a constitutive promoter was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
43
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 33 publications
0
43
0
2
Order By: Relevance
“…There, promoter sequences of bioBbme (396 bp), bioYbme (372 bp), and bioRbme (377 bp) were synthesized by integrated DNA technology (IDT) and encoded by the following three plasmids: pIDT-PbioBbme, pIDT-PbioYbme, and pIDT-PbioRbme (Table 1). Subsequently, the promoter regions were cut from the pIDT vector with SmaI and BamHI and cloned into pRG970, a low-copy-number lacZ reporter vector (42,43), via the same cuts, yielding pRG-PbioBbme, pRGPbioYbme, and pRG-PbioRbme, respectively ( Table 1). All the required recombinant plasmids were verified by either PCR detection, digestion of restriction enzymes, or direct DNA sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…There, promoter sequences of bioBbme (396 bp), bioYbme (372 bp), and bioRbme (377 bp) were synthesized by integrated DNA technology (IDT) and encoded by the following three plasmids: pIDT-PbioBbme, pIDT-PbioYbme, and pIDT-PbioRbme (Table 1). Subsequently, the promoter regions were cut from the pIDT vector with SmaI and BamHI and cloned into pRG970, a low-copy-number lacZ reporter vector (42,43), via the same cuts, yielding pRG-PbioBbme, pRGPbioYbme, and pRG-PbioRbme, respectively ( Table 1). All the required recombinant plasmids were verified by either PCR detection, digestion of restriction enzymes, or direct DNA sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…Glutamate that is formed by the oxidation of proline eventually enters the tricarboxylic acid cycle via ␣-ketoglutarate. Proline catabolism has been shown to be an important energy pathway in various gramnegative bacteria such as Bradyrhizobium japonicum, Sinorhizobium meliloti, and Helicobacter pylori, with proline serving as a preferred respiratory substrate in various environments (12,25,38,58,59).…”
mentioning
confidence: 99%
“…In contrast to only a few studies on genetically engineered yeasts, many studies on genetically engineered bacteria have been reported, such as Pseudomonas strains used for bioremediation and lactic acid bacteria used for probiotics (1,7,19,21). Specific methods for the detection of genetically engineered bacteria have been reported previously (11,26,27,30).…”
mentioning
confidence: 99%